해석 기법 별 유체 슬로싱 현상에 대한 비교 분석 - 장유진(Y.J. Jang) (한국전산유체공학회지, 2020)
In a swaying tank partially filled with liquid, inertia of the liquid exerts body force on itself, causing a periodic motion of the free surface of the liquid. This might cause the tank sway, which leads to structural damages of it. This phenomenon is called “Liquid Sloshing.” Many researches on liquid sloshing including experiments were conducted through numerical methods like Finite Volume Method(FVM), Finite Element Method(FEM), and Smoothed Particle Hydrodynamics(SPH) Method and so on. Except for particle-based numerical methods, other numerical methods are required to simulate free surface shape of liquid. These grid-based methods use Volume of Fluid method(VOF) or Level-set method to imitate the free surface shape. In this Paper, It aims to simulate sloshing phenomena of 3-dimensional rectangular tank. FVM and VOF method, FEM and Level-set method, and a particle-based solver with SPH method are used for analyzing sloshing motions. The CFD results are compared with experimental data and other published computational data. The details of time history pressure data on the tank wall and the free surface shape are discussed to find characteristics of the numerical methods. KCI Citation Count: 0